Is the Price Level in Norway Determined by Fiscal Policy? - Ragna Alstadheim (Norges Bank, 2005)
The Norwegian public sector has net financial assets. The fiscal theory of price determination applies equally to Norway and economies with net public debt: If primary surpluses evolve independently of nominal debt (or assets), the price level has to adjust to satisfy the intertemporal budget constraint of the public sector. In this 'non-Ricardian' regime, monetary policy cannot provide the nominal anchor. In the alternative 'Ricardian' regime, surpluses respond to debt, and monetary policy is the nominal anchor. The plausibility of NR regimes is disputed. I use fiscal data and oil prices to argue that the Norwegian regime is Ricardian.
hdl:11250/2498442
Keywords: E60; E63; 330; Ricardian regime; price level determinacy; fiscal policy; nominal anchor